Immunological Insights into Rheumatoid Arthritis: A Comprehensive Review of Diagnosis and Assessment Approaches - Abdullah Salim Al-Karawi; Yamama Farouk Alawssi; Maha Khalid Khadhum (African Journal of Advanced Pure and Applied Sciences, 2023)
This comprehensive review addresses the challenges and future prospects of immunological approaches in the management of Rheumatoid Arthritis (RA). It begins with an introduction to RA as a chronic autoimmune disease characterized by joint inflammation. The complexities of RA diagnosis are emphasized, followed by an exploration of the challenges surrounding treatment response heterogeneity, drug safety, primary non-response and secondary loss of response, optimal timing of therapy initiation, and cost accessibility. The review highlights ongoing efforts to identify biomarkers for personalized therapy, understand underlying mechanisms to enhance treatment efficacy, and optimize patient outcomes. Future perspectives include advancements in precision medicine tailored to individual patients and the development of novel therapeutics targeting specific immune pathways or cell subsets. Continued research collaboration is pivotal for optimizing RA care.